Assessing psychological variables on mobile devices: an introduction to the experience sampling app ESM-Quest - Goetz, Thomas; Steiner, Wolfgang; Graf, Elisabeth; Stempfer, Lisa; Ristl, Christina; Rupprecht, Fiona S.; Donath, Johanna L.; Botes, Elouise; Nikitin, Jana (Frontiers in Psychology, 2024)
The use of the Experience Sampling Method (ESM), which involves repeated assessments in people’s daily lives, has increased in popularity in psychology and associated disciplines in recent years. A rather challenging aspect of ESM is its technical implementation. In this paper, after briefly introducing the history of ESM and the main reasons for its current popularity, we outline the ESM-Quest experience sampling app which is currently being developed at the University of Vienna. ESM-Quest runs on different operating systems, specifically on mobile devices such as smartphones and tablets running either iOS or Android. An internet connection is not necessary during the assessment. Compared to most other ESM apps, ESM-Quest allows event-based random sampling, which is very helpful when assessments need to be collected within specific situations. Currently, ESM-Quest is being utilized at the University of Vienna and will be made available for research groups worldwide upon request. We introduce the technical aspects of ESM-Quest and provide examples of analyses on ESM data collected through this app, such as examining fluctuations in constructs within individuals. Finally, we outline potential next steps in ESM research.